Structural Model of Motor Readiness of Young Gymnasts Aged 6-8 - Худолій, О.; Карпунець, Т.; Іващенко, О. (Physical Education Theory and Methodology, 2015)
The purpose of the research is to determine the factor structure of the motor readiness of young gymnasts aged 6—8. Research methods. To achieve the tasks set, the research relies on theoretical and empirical methods used: analysis and collation of scientific and methodological literature; modeling, pedagogical observations and experiment, factor analysis. The research recorded the following indicators: the number of repetitions required to teach the exercises; score for the unit-directional movement coordination exercise (test 3); score for the differently directed movement coordination exercise (test 4); error in spatial precision of hand movements (test 9); error in spatial accuracy of leg movements (test 14); error in time accuracy of executing the sitting-to-lying event (test 17); error in time accuracy of five jumps on marks in 5 seconds (test 18); error in evaluation of muscular efforts with visual control (test 24); error in evaluation of muscular efforts without visual control (test 25); vestibular stability, error (test 28); wrist strength; back strength; standing long jump. The participants in the study were 40 gymnasts aged 6-7 and 32 gymnasts aged 7-8. Research results. The young gymnasts aged 6-8 have quite distinct elements that determine the development of their sports skills, namely: learning ability, motor experience, coordination complexity of exercises; relationship between the strength development and the ability to differentiate muscular efforts; movement coordination, movement control and vestibular apparatus stability.